Strategi pemasaran Roti Ganjel Rel sebagai objek wisata gastronomi di kota Semarang Jawa Tengah - Adiyanti, Assyifa Shafia; Disma, Fatimatuz Zahra; Turgarini, Dewi; Kusumati, Pippin (Jurnal Pariwisata Tourista, 2024)
The trend of culinary tourism is growing with cities seeking to explore the richness of their culinary culture. However, challenges arise in maintaining the sustainability of traditional foods amidst diverse consumer preferences. It is crucial for traditional food vendors to innovate, maintain quality, and keep prices stable to stay appealing, as seen in efforts to preserve Roti Ganjel Rel as a unique culinary attraction in Semarang. This study uses a qualitative approach to examine the preservation of traditional food culture of Roti Ganjel Rel and its marketing strategies in Semarang, utilizing interviews, literature reviews, documentation studies, and questionnaires. The study aims to develop marketing strategies to enhance the gastronomic appeal of Roti Ganjel Rel. Through SWOT Matrix analysis, important insights are gained to address product portion and texture variability by developing more consistent production standards, product diversification, improving production capacity, and supply chain efficiency. Growth opportunities exist through education, promotion, and product innovation, despite threats from product competition and market uncertainty. It is also recommended to leverage social media advertising services and enhance brand image through customer reviews on platforms.